2019
DOI: 10.1002/jcla.22867
|View full text |Cite
|
Sign up to set email alerts
|

Association of PON1 gene promoter DNA methylation with the risk of Clopidogrel resistance in patients with coronary artery disease

Abstract: Background and AimsThe failure of therapeutic response to clopidogrel in platelet inhibition, which is called clopidogrel resistance (CR), is more likely to cause cardiovascular events. We aimed to study the contribution of promoter DNA methylation of paraoxonase 1 (PON1) to the risk of clopidogrel poor response.MethodsThrough VerifyNow P2Y12 assay, patient’ platelet functions were measured. Among 57 non‐CR and 49 CR patients, the levels of DNA methylation in four CpG dinucleotides on the PON1 promoter were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 44 publications
(65 reference statements)
1
42
1
Order By: Relevance
“…Clopidogrel is a prodrug, it needs to be metabolized into an active metabolite with the activity of cytochrome P450 and paraoxonase to playing the role of antiplatelet aggregation (9). The variants of cytochrome P450 and paraoxonase can lead to the change of enzyme activity, especially the mutation of CYP2C19*2, CYP2C19*3, PONQ192R allelic [17,18]. The probe drug could be used to measure the activity of CYP450 and to point out the genotyping of CYP450 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Clopidogrel is a prodrug, it needs to be metabolized into an active metabolite with the activity of cytochrome P450 and paraoxonase to playing the role of antiplatelet aggregation (9). The variants of cytochrome P450 and paraoxonase can lead to the change of enzyme activity, especially the mutation of CYP2C19*2, CYP2C19*3, PONQ192R allelic [17,18]. The probe drug could be used to measure the activity of CYP450 and to point out the genotyping of CYP450 [19].…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation reported that aberrant DNA methylation might participate in the occurrence and development of atherosclerotic plaques and coronary heart disease . Furthermore, some studies have demonstrated that changes in ABCB1, ABCC3, P2Y12, and PON1 promoter methylation levels were associated with a decline in clopidogrel antiplatelet effects.…”
Section: Discussionmentioning
confidence: 99%
“…26 and coronary heart disease. 27 Furthermore, some studies have demonstrated that changes in ABCB1, 28 ABCC3, 29 P2Y12, 17 and PON1 18 promoter methylation levels were associated with a decline in clopidogrel antiplatelet effects.…”
Section: Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that epigenetic modifications in the promotor or coding region, in response to certain physiologic or pathophysiologic states, can either activate or silence certain CYP450 enzymes. For example, methylation of CpG motifs (CpG11, CpG12, CpG13) in the promoter region for CYP2C19 was associated with HTPR and increased risk of ischemic events on clopidogrel [7,85,86]. If an allele is preferentially silenced via epigenetic modifications in the coding region, the complementary allele will be predominantly expressed.…”
Section: Epigenomicsmentioning
confidence: 99%